2009
DOI: 10.1002/jrs.2331
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering investigation of selenomethionine replacement in protein SOUL crystals

Abstract: The vibrational properties of both wild-type and selenomethionine (SeMet)-substituted protein SOUL crystals have been investigated here by Raman spectroscopy. Several Raman peaks observed in the spectra of methionine and SeMet were identified as specific markers. The unambiguous assignment of these peaks has been inferred by comparing the experimental Raman spectra of the pure amino acids, recorded in solid state and in aqueous solution, and the Raman intensities computed using quantum chemical calculations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, very few Raman studies have been reported to date for the solid crystalline form of l-methionine. Using unpolarized light, one compared the solid-state spectra at 273 and 323 K [14], and the other the spectra observed from solid-states samples and water solutions to theoretical spectra of the single-molecules obtained by quantum chemical calculations [15]. Combining IR and Raman spectroscopy to semi-empirical MNDO conformational analysis [14], it was shown that the phase transition observed by means of calorimetric measurements [16,17] on powder samples at about 307 K is related to the existence of a slightly modified H-bonded double layer giving rise to similar lattice vibrations in both phases.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, very few Raman studies have been reported to date for the solid crystalline form of l-methionine. Using unpolarized light, one compared the solid-state spectra at 273 and 323 K [14], and the other the spectra observed from solid-states samples and water solutions to theoretical spectra of the single-molecules obtained by quantum chemical calculations [15]. Combining IR and Raman spectroscopy to semi-empirical MNDO conformational analysis [14], it was shown that the phase transition observed by means of calorimetric measurements [16,17] on powder samples at about 307 K is related to the existence of a slightly modified H-bonded double layer giving rise to similar lattice vibrations in both phases.…”
Section: Introductionmentioning
confidence: 99%
“…There is no obvious visible distortion in the optimized curve either. The prominent Raman peaks of SAM at about 677, 729, 1041, 1324, 1405, 1510, and 2920 cm −1 were assigned to ν (CS), ν s (CN), ω (CH2), ν (CC), ν as (CN), and ν (CH 3 ), respectively [22, 23]. The radius of RCF, as a key parameter, was analyzed to achieve the optimal results.…”
Section: Resultsmentioning
confidence: 99%
“…This spectral feature can be confidently assigned to the C-Se stretching, in agreement with previous Raman studies on selenium-containing organic compounds (Hamada & Morishima, 1977;Paetzold et al, 1967), and on the selenomethionine aminoacid (Zainal & Wolf, 1995;Lopez et al, 1981). Using these assignments, SeMet Raman peaks have been observed also in the SeMet derivative of protein SOUL (Rossi et al, 2009). In these crystals, a quantitative evaluation of the relative amount of SeMet replacement was also achieved by comparative analysis.…”
Section: Raman Detection Of Se-met Incorporation Into Protein Crystalsmentioning
confidence: 99%